2022
DOI: 10.3390/cancers15010018
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analysis of TCGA Data Using Over- and Under- Mutated Genes Identify Key Molecular Pathways and Cellular Functions in Lung Cancer Subtypes

Abstract: We identify critical conserved and mutated genes through a theoretical model linking a gene’s fitness contribution to its observed mutational frequency in a clinical cohort. “Passenger” gene mutations do not alter fitness and have mutational frequencies determined by gene size and the mutation rate. Driver mutations, which increase fitness (and proliferation), are observed more frequently than expected. Non-synonymous mutations in essential genes reduce fitness and are eliminated by natural selection resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The initial dataset consisted of 17,112 genes. The mutational but not expression component of the dataset has been previously investigated [ 9 , 10 ]. Of these, 15,487 genes met our expression-level criterion for inclusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial dataset consisted of 17,112 genes. The mutational but not expression component of the dataset has been previously investigated [ 9 , 10 ]. Of these, 15,487 genes met our expression-level criterion for inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…We note that our methodology for identifying evolutionary selection of gene mutations assumes a roughly equal probability for mutations in all base pairs and, therefore, differs from prior studies that find variation in mutation rates related to gene expression and chromosomal location [ 16 ]. However, as discussed in prior publications [ 9 , 10 ], variation in the observed mutation rates of individual genes resulting from decreased fitness with loss of the cell due to evolutionary selection could be interpreted as the result of intra-genomic variation in mutation rates. For example, Monroe et al [ 17 ], observed that, in Arabidopsis thaliana “genes subject to stronger purifying selection have a lower mutation rate.” In our hypothesis, important regions of the genome are observed to be mutated less often [ 18 ] because such mutations reduce fitness and proliferation and, therefore, not transmitted across generations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation